Formulasi dan Aktivitas Antibakteri Gel Ekstrak Daun Murbei (Morus alba L.) terhadap Staphylococcus aureus - Akbar Rino Pamuladiman; Lina Widiyastuti (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Mulberry leaves (Morus alba L.) contain quercetin, a ﬂavonoid compound with antibacterial activity against Staphylococcus aureus. For convenience, dosage accuracy, and hygiene, a gel formulation with a mixture of carbopol and propylene glycol is required. This study aimed to determine the right concentration of carbopol and propylene glycol to obtain a gel with good physical properties and antibacterial activity on Staphylococcus aureus. Mulberry leaf extract was obtained by maceration method. A factorial design method was used to optimize carbopol and propylene glycol concentrations. The parameters of gel physical properties were the viscosity, spreadability, adhesion, and pH test. The optimal area was determined by creating a contour plot of the parameters test result. Validation of the optimum formula was by comparing the prediction result to the actual research result. The data were analyzed using SPSS with a 95% conﬁdence level. The results showed that the concentration of carbopol and propylene glycol was 1.04% and 7.85%, 1832.42 ± 62.48 cP viscosity, 5.96 ± 0.08 cm spreadability, 64.63 ± 0.97 seconds of adhesion, and pH 5.26 ± 0.03. The antibacterial test showed an inhibitory power with 28.67 ± 0.76 mm. From the teat result, it can be concluded that the gel had antibacterial activity and good physical properties.